1974
DOI: 10.1136/bjo.58.9.798
|View full text |Cite
|
Sign up to set email alerts
|

Management of the dry eye in Sjogren's syndrome.

Abstract: In this paper we report the efficacy of carefully controlled standard forms of treatment in the keratoconjunctivitis (KCS) of Sj0gren's syndrome (SS). Since it is accepted that SS is a chronic benign inflammatory disease characterized by remissions and exacerbations, the results of this study have been withheld until several years have elapsed. For this reason also we make no attempt to comment on forms of treatment such as hydrophilic contact lenses (Gasset and Kaufman, 1971;Krejci, 1972) or motorized fluid d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

1977
1977
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 4 publications
1
13
0
Order By: Relevance
“…They reported that the healing of normal superficial epithelial ulcers is not affected by acetylcysteine. The nontoxicity and some improving effects of acetylcysteine in the present study are slightly similar to those of Absolon and Brown [4], Brown and Weller [7], Berman [11], Williamson et al [9], Frauenfelder et al [12], Marsh and Cooper [13], Burns et al [24], Sugar and Waltman [16] and Petroutsos et al [15].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…They reported that the healing of normal superficial epithelial ulcers is not affected by acetylcysteine. The nontoxicity and some improving effects of acetylcysteine in the present study are slightly similar to those of Absolon and Brown [4], Brown and Weller [7], Berman [11], Williamson et al [9], Frauenfelder et al [12], Marsh and Cooper [13], Burns et al [24], Sugar and Waltman [16] and Petroutsos et al [15].…”
Section: Discussionsupporting
confidence: 76%
“…Williamson et al [9] reported that 20 of the 98 patients (suffering from Sjögren's syndrome and keratoconjunctivitis sicca) who had not responded to tear substitute therapy or nasolacrimal canalicular obliteration were treated with a 5% acetylcysteine solution, pH 8.4 for 1 year. 30% of the cases in this group improved in both symptoms and signs.…”
Section: Discussionmentioning
confidence: 99%
“…Our maximum dose of 20 mM NAC is equivalent to a 0.33% solution, which is much lower than the solutions used clinically. Although, in clinical studies, topical applications of 5 and 20% NAC have been shown to be effective in the treatment of Sjogren syndrome 22 and long-standing corneal epithelial defects, 23 respectively, without toxic effects, the reports on animal experimental studies are contradictory. In all, 3% NAC has been shown to reduce the healing time in dog and rabbit corneas 12,13 whereas 10 and 20% concentrations had no effect in dogs.…”
Section: Discussionmentioning
confidence: 93%
“…The safety profile of this medication is consistent with previously reported studies using NAC topically on the ocular surface. [30][31][32] Current contact lens cleaning solutions available have been shown to remove daily accumulation of lysozyme, lactoferrin, and lipocalin. 20 Full-time contact lens wear has the disadvantage of protein buildup due to the deviation from preferred daily contact lens removal and cleaning protocols.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there have been numerous studies touting the efficacy of topical or oral N-acetylcysteine (NAC) for decreasing ocular mucous plaques/buildup on the corneal surface in such diseases as keratoconjunctivitis sicca, meibomian gland dysfunction, and Sjogren's syndrome. [30][31][32][33][34] However, NAC is more commonly utilized for reducing pulmonary mucous plugging and as a treatment for acetaminophen overdose. [35][36][37][38] NAC functions as an antioxidant 39 and this study addresses the potential effect on the ocular surface.…”
Section: Introductionmentioning
confidence: 99%